Association between polymorphic CAG repeat lengths in the androgen receptor gene and susceptibility to prostate cancer: A systematic review and meta-analysis. Issue 25 (June 2017) - Qin, Zhiqiang; Li, Xiao; Han, Peng; Zheng, Yuxiao; Liu, Hanyu; Tang, Jingyuan; Yang, Chengdi; Zhang, Jianzhong; Wang, Kunpeng; Qi, Xiaokang; Tang, Min; Wang, Wei; et al.
Abstract: Background: Previous studies have been conducted to reveal the relationship between androgen receptor CAG polymorphism and risk of prostate cancer, yet the results were elusive and controversial. Thus, this meta-analysis was performed to clarify this association. Methods: To obtain the relevant available studies, online databases PubMed, Embase, and Web of science were searched until September 1st, 2016. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength of such association. Subgroup analyses were conducted based on ethnicity and source of controls. Moreover, Begg's funnel plots and Egger's linear regression test were conducted to test the publication bias. Results: Overall, our results enrolled 51 studies indicated that significant increased risk of prostate cancer was associated with androgen receptor CAG polymorphism (OR  =  0.77, 95% CI: 0.67–0.89). In addition, compared with CAG repeat <20, 22, carriers of ≧20, 22 repeats had decreased risk of prostate cancer (cut-off point  =  20: OR  =  0.27, 95% CI: 0.13–0.52; cut-off point  =  22: OR  =  0.82, 95% CI: 0.70–0.97). However, when cut-off point  =  23, no significant result was detected in such association (pooled OR  =  0.88, 95% CI: 0.63–1.24). When cut-off point is 22, the results were positive only in Asian population (OR  =  0.53, 95% CI: 0.32–0.89) in the subgroup analysis by ethnicity. Besides, when the studies were stratified by source of controls, the results were not significant in both the subgroup of population-based controls and hospital-based controls. Conclusions: This meta-analysis suggested the carriers of short polymorphic CAG repeats might increase susceptibility to prostate cancer, which held potential as a detecting marker of the risk of prostate cancer.